Pendampingan Kelompok Sosial Rukun Warga Berbasis Siaga Kelurahan Tobekgodang Kecamatan Binawidya Kota Pekanbaru - Aguswan; Widia Astuti; Trio Saputra (LPPM UMRI, 2021)
Assistance for the RW Siaga group in the utilization of the RW (15) yard of Tobekgodang Sub-district, Binawidya District, Pekanbaru City. Mentoring is carried out in the standby-based community group of Rukun Warga that has been determined by the Tobekgodang village head regarding the Appointment of the Standby Residents' Association Board. The purpose of the assistance is to assist the RW Siaga (RW.15) management or group in the use of mosque yard land for planting live pharmacies, living stalls, fisheries that preserve the environment, increasing public health awareness. The method in carrying out activities is to invite and gather administrators and group members, socialization of land use, field work practices. The desired achievement is the strengthening of vigilant community groups to be able to use clean and beautiful environmental yards so that the realization of a community that cares about environmental health based on community harmony standby in RW (15) Tobekodang Subdistrict, Binawidya District, Pekanbaru City.